Non-cyanobacterial diazotrophs support the survival of marine microalgae in nitrogen-depleted environment - Udita Chandola; Marinna Gaudin; Camille Trottier; Louis-Josselin Lavier-Aydat; Eric Manirakiza; Samuel Menicot; Erik Jörg Fischer; Isabelle Louvet; Thomas Lacour; Timothée Chaumier; Atsuko Tanaka; Georg Pohnert; et al. (Genome Biology)
Abstract Background Non-cyanobacteria diazotrophs (NCDs) are shown to dominate in surface waters shifting the long-held paradigm of cyanobacteria dominance. This raises fundamental questions on how these putative heterotrophic bacteria thrive in sunlit oceans. The absence of laboratory cultures of these bacteria significantly limits our ability to understand their behavior in natural environments and, consequently, their contribution to the marine nitrogen cycle. Results Here, via a multidisciplinary approach, we identify the presence of NCDs within the phycosphere of the model diatom Phaeodactylum tricornutum (Pt), which sustain the survival of Pt in nitrogen-depleted conditions. Through bacterial metacommunity sequencing and genome assembly, we identify multiple NCDs belonging to the Rhizobiales order, including Bradyrhizobium, Mesorhizobium, Georhizobium, and Methylobacterium. We demonstrate the nitrogen-fixing ability of PtNCDs through in silico identification of nitrogen fixation genes and by other experimental assays. We show the wide occurrence of this type of interactions with the isolation of NCDs from other microalgae, their identification in the environment, and their predicted associations with photosynthetic microalgae. Conclusions Our study underscores the importance of microalgae interactions with NCDs to support nitrogen fixation. This work provides a unique model Pt-NCDs to study the ecology of this interaction, advancing our understanding of the key drivers of global marine nitrogen fixation.